Exercise training reduces insulin resistance in postmyocardial infarction rats. Issue 4 (23rd April 2015) - Wang, Youhua; Tian, Zhenjun; Zang, Weijin; Jiang, Hongke; Li, Youyou; Wang, Shengpeng; Chen, Shengfeng
Abstract Myocardial infarction (MI) induces cardiac dysfunction and insulin resistance (IR). This study examines the effects of MI‐related IR on vasorelaxation and its underlying mechanisms, with a specific focus on the role of exercise in reversing the impaired vasorelaxation. Adult male Sprague–Dawley rats were divided into three groups: Sham, MI, and MI+Exercise. MI+Exercise rats were subjected to 8 weeks of treadmill training. Cardiac contraction, myocardial and arterial structure, vasorelaxation, levels of inflammatory cytokines, expression of eNOS and TNF‐α, and activation of PI3K/Akt/eNOS and p38 mitogen‐activated protein kinase (p38 MAPK) were determined in aortas. MI significantly impaired endothelial structure and vasodilation (P < 0.05–0.01), as indicated by decreased arterial vasorelaxation to ACh and insulin. MI also attenuated the myocardial contractile response, decreased aortic PI3K/Akt/eNOS expression and phosphorylation by insulin, and increased IL‐1β, IL‐6, and TNF‐α expression and p38 MAPK activity (P < 0.05–0.01). Exercise improved insulin sensitivity in aortas, facilitated myocardial contractile response and arterial vasorelaxation to ACh and insulin, and increased arterial PI3K/Akt/eNOS activity. Moreover, exercise markedly reversed increased p38 MAPK activity and normalized inflammatory cytokines in post‐MI arteries. Inhibition of PI3K with LY‐294002, and eNOS with L‐NAME significantly blocked arterial vasorelaxation and PI3K/Akt/eNOS phosphorylation in response to insulin. In conclusion, these results demonstrate that endothelial dysfunction in response to insulin plays an important role in MI‐related IR. The reversal of IR by exercise is most likely associated with normalizing inflammatory cytokines, increasing the activation of PI3K/Akt/eNOS, and reducing the activation of p38 MAPK.